A Contrastive Analysis of Adjuncts Regarding their Manner of Expression in English and Persian. (24th June 2015) - Mirzahoseini, Zeinab; Gowhary, Habib; Jamalinesari, Ali; Azizifar, Akbar
Abstract: The present study aims at investigating the manner of expression of adjuncts in English and Persian based on (Halliday, 2004 ). Halliday's categorization of adjuncts into "interpersonal, textual, and experiential" was adopted to classify the collected examples of adjuncts . Some English novels and their Persian translations were investigated and more than 220 adjuncts were identified in the two languages. Based on (Halliday, 2004 ), these adjuncts were categorized into "interpersonal, experiential and textual". By employing descriptive and inferential statistics, the results were analyzed. The findings obtained by running statistical operations revealed that English and Persian use almost the similar tools (adverbial, prepositional phrase, and clause) to express experiential adjuncts . However, it was found that the two contrasted languages do not use the same linguistic tools to express interpersonal and textual adjuncts .